Etiology and Recovery of Neuromuscular Fatigue following Competitive Soccer Match-Play - Brownstein, Callum G.; Dent, Jack P.; Parker, Paul; Hicks, Kirsty M.; Howatson, Glyn; Goodall, Stuart; Thomas, Kevin (Frontiers in Physiology, 2017)
Aim: Previous research into the etiology of neuromuscular fatigue following competitive soccer match-play has primarily focused on peripheral perturbations, with limited research assessing central nervous system function in the days post-match. The aim of the present study was to examine the etiology and time-course of recovery of neuromuscular fatigue following competitive soccer match-play. Methods: Sixteen male semi-professional soccer players completed a 90-min soccer match. Pre-, post- and at 24, 48 and 72 h participants completed a battery of neuromuscular, physical and perceptual tests. Maximal voluntary contraction force (MVC) and twitch responses to electrical (femoral nerve) and magnetic (motor cortex) stimulation (TMS) during isometric knee-extension and at rest were measured to assess central nervous system (voluntary activation, VA) and muscle contractile (potentiated twitch force, Qtw,pot) function. Electromyography responses of the rectus femoris to single- and paired-pulse TMS were used to assess corticospinal excitability and short-interval intracortical inhibition (SICI), respectively. Fatigue and perceptions of muscle soreness were assessed via visual analogue scales, and physical function was assessed through measures of jump (countermovement jump height and reactive strength index) and sprint performance. Results: Competitive match-play elicited significant post-match declines in MVC force (−14%, P < 0.001) that persisted for 48 h (−4%, P = 0.01), before recovering by 72 h post-exercise. VA (motor point stimulation) was reduced immediately post-match (−8%, P < 0.001), and remained depressed at 24 h (−5%, P = 0.01) before recovering by 48 h post-exercise. Qtw,pot was reduced post-match (−14%, P < 0.001), remained depressed at 24 h (−6%, P = 0.01), before recovering by 48 h post-exercise. No changes were evident in corticospinal excitability or SICI. The temporal pattern in recovery of jump performance and neuromuscular function was similar, while perceptions of fatigue persisted at 72 h. Conclusion: Competitive soccer match-play elicits substantial impairments in central nervous system and muscle function, requiring up to 48 h to resolve. The results of the study have important implications for fixture scheduling, the optimal management of the training process, squad rotation during congested competitive schedules, and the implementation of appropriate recovery interventions.